Characterization of VIM-1-Producing E. coli Isolated From a German Fattening Pig Farm by an Improved Isolation Procedure - Irrgang, A.; Tenhagen, B.-A.; Pauly, N.; Schmoger, S.; Kaesbohrer, Annemarie; Hammerl, J. A. (Frontiers in Microbiology, 2019)
A few reports indicate that livestock might represent a new reservoir for carbapenemase-producing Enterobacteriaceae (CPE). In 2015, VIM-1-producing Escherichia coli were detected at slaughter in colon contents of animals from a German fattening pig farm within the national monitoring on ESBL-producing E. coli. In this study, pooled faces samples from pigs, as well as samples from the barn surrounding environment of this fattening farm were taken, to evaluate the dissemination of CPEs. Several modifications of the culture-dependent detection procedure were investigated for their potential to improve the sensitivity of the CPE isolation method. The current reference procedure was adapted by adding a real-time PCR pre-screening and additional enrichment steps. It was possible to isolate 32 VIM-1-producing E. coli from four fecal samples of three different barns using two serial enrichment steps in combination with real-time PCR and selective agar plates. By genetic typing methods, we confirmed the presence of two E. coli clonal lineages circulating on this particular farm: one was harboring the blaVIM-1 on an IncHI2 plasmid while the second lineage carried the gene on the chromosome. Despite its different locations, the blaVIM-1 gene was harbored on a class 1 integron in both clonal lineages. Whole-genome sequencing revealed that the VIM-1 carrying plasmids exhibited only slight variability in its compositions and sizes. We assume that the prevalence of CPEs in animal production in Germany and other European countries might be underestimated and there is a concern of further spread of VIM-1-producing bacteria in German livestock and food.